Pengaruh Konsentrasi Benzyl Amino Purin dan Indole Acetic Acid dalam Multiplikasi Tunas Pisang Merah (Musa acuminata Red Dacca) Asal Banten Secara in Vitro - Irfan Anshori; Sulastri Isminingsih; Nurmayulis Nurmayulis; Susiyanti Susiyanti (Jurnal Agroekoteknologi, 2022)
This study aimed to determine the response of red banana shoots (Musa acuminata Red Dacca) origin from Banten in vitro due to administration of benzyl amino purin (BAP) and indole acetic acid (IAA) in various concentrations. This research was conducted at the Laboratory of Biotechnology and Plant Physiology, University of Sultan Ageng Tirtayasa from March 2022 to May 2022. The research design used was a factorial randomized completely block design consisting of two factors. The first factor is the concentration of BAP which consists of theree levels, namely 0 mg kg-1, 2 mg kg and 4 mg kg-1. The second factor is the concentration of IAA which consists of theree levels, namely 0 mg kg-1, 0.25 mg kg-1 and 0.50 mg kg-1. The concentration of 2 mg kg-1 BAP gave the best results on the parameters of the number of shoots aged 2 weeks after planting (WAP) (2.06 shoots), 4 WAP (2.38 shoots) and 6 WAP (2.50 shoots), the number of leaves aged 2 WAP (1.34 strands), 4 WAP (1.91 strands), 6 WAP (2.16 strands). The concentration of IAA 0 mg kg-1 gave the best results on the parameter of the number of leaves at 2 WAP (1.36 strands). Indole acetic acid concentration of 0.25 mg kg-1 gave the best results on the parameters ofthe number of roots aged 2 WAP (1.50 roots), 4 WAP (1.65 roots) and 6 WAP (1.78 roots). There was no interaction between the two treatments.